PENGGUNAAN METODE DESIGN THINKING UNTUK PENGEMBANGAN STANDAR OPERASIONAL PROSEDUR PADA USAHA TOKO ROTI ABANA KITCHEN - Yudistya Wardhana, Daniel; Hariwibowo, Ignatius Novianto (Universitas katolik Musi Charitas, 2023)
The development of the culinary business in DIY had experienced heavy pressure during thepandemic. Along with the recovery of economic activities, culinary businesses are facing changes inconsumer tastes that need to be faced by business actors. Abana Kitchen is one of the businesses thatfaces the challenge of adjusting business processes needed to adjust conditions after the pandemic.Therefore, this devotion is done to help Abana Kitchen to adjust business processes. This service usesa design thinking approach in the preparation of new business processes, which consist of 5 stages,namely: empathize, define, idiate, prototype, test. The result of this devotion is a new business processthat suits the needs of Abana Kitchen, which is business management activity that aligned withproduct standarization that produce high quality products.